2013
DOI: 10.5539/ass.v9n5p203
|View full text |Cite
|
Sign up to set email alerts
|

A Documentary Analysis of the Government’s Circulars on Positive Behavior Enhancement Strategies

Abstract: This paper analyses the concept of positive behavior and strategies for promoting positive behavior in a country that has a centralized educational system, namely Malaysia. The analysis covers 91 circulars (official government documents) that were distributed to schools over a period of 40 years (from 1969 to 2011). The analysis uses a content analysis approach. The results suggest that the concept of positive behavior revolves around discipline and obedience. The term 'good discipline' is frequently used refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Their ability and wisdom in handling learning activities will have a direct impact on students' active involvement in learning activities. Therefore, the development of teachers competency involving the efforts of fostering positive attitudes (Awang, Jindal-Snape & Barber, 2013) was a major agenda to strengthen the teaching profession and to ensure great development of the education quality in many countries around the world. In the Indonesian context, the government has set specific standards in determining the implementation of quality education in accordance with the education laws which related to education curriculum, competency of teachers, educational infrastructure, organization of learning activities and educational assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Their ability and wisdom in handling learning activities will have a direct impact on students' active involvement in learning activities. Therefore, the development of teachers competency involving the efforts of fostering positive attitudes (Awang, Jindal-Snape & Barber, 2013) was a major agenda to strengthen the teaching profession and to ensure great development of the education quality in many countries around the world. In the Indonesian context, the government has set specific standards in determining the implementation of quality education in accordance with the education laws which related to education curriculum, competency of teachers, educational infrastructure, organization of learning activities and educational assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Norlander (2009) suggests that effective teacher is a person who is able to carry out his duties and responsibilities successfully. Past studies showed that effective teachers must have broad knowledge and pedagogical skills to promote appropriate behaviour (Awang, Jindal-Snape, & Barber, 2013). Public assumes that being a teacher is an easy job.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong association between individuals' attitudes towards education and their academic performance and commitment. Students who have negative attitudes towards education activities are found to exhibit challenging behaviour including anti-social and off-task behaviour (Awang, Jindal-Snape& Barber, 2013). Ming, Ling and Jaafar (2011) found that streaming in education has a close relationship with students' academic achievement.…”
Section: Students' Attitudes and Academic Achievement In Nationhood Ementioning
confidence: 99%